2010
DOI: 10.1183/09031936.00174609
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory chemoresponsiveness, narcolepsy–cataplexy and human leukocyte antigen DQB1*0602 status

Abstract: We hypothesised that hypocretin (orexin) plays a role in the determination of ventilatory chemosensitivity. 130 patients with narcolepsy-cataplexy (mean¡SD age 20¡10 yrs, 69% male) and 117 controls (22¡6.9 yrs, 62% male) were recruited and tested for human leukocyte antigen (HLA)-DQB1*0602 status, hyperoxia hypercapnic (change in minute ventilation (DV9E)/carbon dioxide tension (DPCO 2 ) L?min KEYWORDS: Chemoresponsiveness, human leukocyte antigen DQB1, hypercapnia, hypoxia, narcolepsy H ypoxic and hypercapnic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 34 publications
1
37
2
Order By: Relevance
“…In contrast to findings suggested by animal gene knock out model, we found no group differences in regard to hypercapnic responsiveness, but rather found significant differences in hypoxic responsiveness. Reduced hypoxic responsiveness in narcolepsycataplexy patients was unrelated to BMI, age, and sex [19].…”
Section: Narcolepsy and Respiratory Control: Human Studymentioning
confidence: 78%
See 1 more Smart Citation
“…In contrast to findings suggested by animal gene knock out model, we found no group differences in regard to hypercapnic responsiveness, but rather found significant differences in hypoxic responsiveness. Reduced hypoxic responsiveness in narcolepsycataplexy patients was unrelated to BMI, age, and sex [19].…”
Section: Narcolepsy and Respiratory Control: Human Studymentioning
confidence: 78%
“…We will also report chemoresponsiveness in patients with narcolepsycataplexy, a human model of orexin deficiency, which indicates an unexpected finding that the mechanism for differences between patients and controls in hypoxic responsiveness could relate to HLA marker status rather than orexin deficiency [19].…”
Section: Introductionmentioning
confidence: 95%
“…Observations of ventilatory responses to these conditions in orexin peptide knockouts and after central administration of orexin peptides has been mixed; some studies have found an involvement of orexin in mediating increased ventilatory responses to hypercapnia (Deng et al, 2007;Nakamura et al, 2007;Dias et al, 2009Dias et al, , 2010Nattie and Li, 2010), decreased pulmonary activity to hypoxia (Deng et al, 2007;Nakamura et al, 2007), or no detectable response to either condition (Zhang et al, 2005). Conversely, a study of patients with narcolepsy-cataplexy detected attenuated responses to hypoxia but not hypercapnia (Han et al, 2010), which is exactly opposite that found in rodent models. Clearly, more work needs to be done to confirm a role for orexin in mediating ventilatory responses to changing blood gas levels as opposed to controlling sleep/ wake cycles to maintain energy homeostasis.…”
Section: B Orexin Influences On Peripheral Physiologymentioning
confidence: 85%
“…For example, it is well known that the neuropeptide orexin contributes to arousal state (26) and that orexinergic neurons are more active in the awake state than during sleep (54). These neurons have widespread projections to the brain stem, including respiratory-related nuclei (43,58), and there is evidence that orexin contributes to chemosensitivity, particularly more in the awake state compared with NREM sleep (17).…”
Section: Discussionmentioning
confidence: 99%